Studies on Essential Oils and DNA Extraction from Ocimum species - Rupal Singh1, Noor Afshan Khan2, Abin Mani1; Jaswant Patel1, Sadaf Quereshi1*, Pankhuri Purwar1 (Journal of Phytology, 2011)
Asia has one of the largest biodiversity regions in the world, holding abundant medicinal and aromatic plant species. The Genus OcimumÃ‚Â is ranked highest among some of the astonishing herbs for having enormous medicinal potentialities. The Ã¢â‚¬Å“Queen of HerbsÃ¢â‚¬Â Tulsi is used as a medicinal plant in India since about five thousand years. The Ocimum essential oils are valued because of their main component, methylchavicol and methyleugenol which possess therapeutic properties. Thus, its major use is in the pharmaceutical industry. In the present paper, extraction of essential oils from three different Ocimum species viz. O. gratissimum, O. sanctum and <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: Calibri; mso-bidi-font-weight: bold; mso-bidi-font-family: ’Arial MT’; mso-ansi-language: EN-IN; mso-fareast-language: EN-IN;" lang="EN-IN">O. americanum were carried out with oil yield of 1.0%, 1.5% and 1.25%, respectively. GC analysis of essential oil indicates the presence of important constituents. TLC of leaf pigments represents the most important pigments followed by TLC of essential oils for determining the presence of alcohols, esters and carbonyl compounds. The plant DNA were isolated with concentration of 200ng/Ã‚Âµl (O. gratissimum), 210ng/Ã‚Âµl (O. sanctum) and 280 ng/Ã‚Âµl (O. americanum), based on spectrophotometric reading.